Dental caries in 12-year-old schoolchildren who participate in a preventive and restorative dentistry program = Caries dental en escolares de 12 años que participan en un programa de odontología preventiva y rehabilitación oral - Ramírez, Karol 1977-
Since 2013, the Faculty of Dentistry of the University of Costa Rica has provided a preventive and restorative oral health program at Carmen Lyra Public School. The first generation of students that received dental care from this project were examined in 2019 for caries status. A total of 62 twelve-year-old schoolchildren were examined (31 boys and 31 girls). First, all teeth surfaces were cleaned with a brush and then rinsed. Subsequently, examination was performed in each person by a calibrated examiner using the International Caries Detection and Assessment System (ICDAS). Prevalence of dental caries was 59.7%. ICDAS code 2 was the most prevalent (68.8%), followed by 1 (19.3%), 5 (4.5%), 3 (3.5%), 6 (2.5%), and 4 (1.4%). Regarding number of carious surfaces, the highest prevalence was observed in the occlusal surfaces (77.3%), followed by the vestibular (13.9%), mesial (4.2%), palatal/lingual (4,1%) and distal (0.5%). Of these carious surfaces, 7% were caries associated with restorations and were present only on the occlusal surfaces. Boys had more cavities than girls (54.1% compared to 45.9%), however, this difference was not significant. Regarding the condition of restorations in teeth, 92 dental restorations (resin or amalgam) were found in the population studied and were well adjusted. Most of these restorations were found on the occlusal surfaces (82.6%), followed by vestibular surfaces (8.7%,) palatal/lingual (5.4%) surfaces, mesial surfaces (3.3%), and no restorations were detected on the distal surfaces. Sealants were identified in 11.3% schoolchildren; 98% were identified on the occlusal surfaces and the other 2% were found on the palatal/lingual surfaces. DMFT Index was 1.6±0.71. The prevalence of dental caries in this sample was low compared to other studies in twelve-year-old schoolchildren in Costa Rica. This may suggest that the oral health program had a positive impact in the studied population.